Human Rights Protection under the Indonesian Constitution: Progress and Challenges - Irman Putra; Arief Fahmi Lubis (West Science Law and Human Rights, 2024)
This paper examines the protection of human rights under the Indonesian Constitution, focusing on the progress that has been made and the challenges faced. Using a combination of juridical analysis and literature review, it evaluates the effectiveness of constitutional provisions designed to protect human rights and their alignment with international standards. The research highlights significant achievements, including including human rights guarantees in the 1945 Constitution and establishing key institutions such as the National Human Rights Commission (Komnas HAM) and the Constitutional Court. Despite these advances, the study identifies persistent problems such as inadequate law enforcement, systemic discrimination, and limited access to justice. These findings underscore the need for better implementation mechanisms, greater institutional support, and targeted policies to address the gap between constitutional ideals and practical outcomes. The paper concludes with recommendations for future research and policy reforms to strengthen human rights protection in Indonesia.